Optimasi Formula Sediaan Losion Ekstrak Bunga Rosella (Hibiscus sabdariffa L.) dengan Box-Behnken Design - Shofiani, Della; Puspita Tanjung, Yenni; Akmal, Tubagus (Jurnal Farmasi (Journal of Pharmacy), 2025)
The extract of roselle flowers contains flavonoid and phenolic components, which function as antioxidants that inhibit free radicals, proving beneficial in avoiding skin degeneration. The antioxidant properties of roselle flowers can be included into cosmetic compositions, including lotions. This study aims to create an optimal lotion formulation by adjusting the quantities of the emulsifiers Olivem®900, Cetearyl alcohol, and TEGO®Care 165. The base formula was optimized using the Box-Behnken Design as an experimental framework, facilitated by Design-Expert version 13.05.0 software. The evaluated response factors comprised pH, viscosity, and spreadability. The formulation was maintained at ambient temperature for 28 days and subsequently evaluated using GraphPad Prism version 10.4.0 software. The base optimization method utilized 15 recommended formulations, determining that the optimal base formula comprises 1.6% Olivem®900, 4.2% Cetearyl alcohol, and 9% TEGO®Care 165, achieving a desirability value of 1. The optimal formula layer derived was the foundation of the lotion including roselle flower extract. The results of the stability test analyzed statistically using the t-test showed differences in the pH test which had a significant effect (p<0.05) between the optimum formula of lotion base and the optimum formula of rosella flower extract lotion, but had no significant effect (p>0.05) on the viscosity test and the spreadability test. The results of the analysis using the t-test showed a significance value of p>0.05, which means that the preparation is statistically stable during the storage period.